Chocolate Milk versus carbohydrate supplements in adolescent athletes: a field based study - Katelyn A. Born; Erin E. Dooley; P. Andy Cheshire; Lauren E. McGill; Jonathon M. Cosgrove; John L. Ivy; John B. Bartholomew (Taylor & Francis Group, 2019)
Purpose The purpose of this study is to translate laboratory-based research on beverage-based supplements to a naturalistic, field setting in adolescent athletes. To this end, we tested the effects of two commercially-available drinks on strength in a field-based setting with both male and female high school athletes completing a summer training program. Methods One hundred and three high school athletes completed the study (M age = 15.3, SD = 1.2; 70.9% male; 37.9% Afr. Amer.). Measures included a composite strength score (bench press + squat). Participants completed 1 week of pre- and post-testing, and 4 days per week of strength and conditioning training for 5 weeks. Participants were randomly-assigned to receive either CM or CHO immediately post-exercise. Results A 2 (group) × 2 (time) repeated measures ANOVA showed there was a significant main effect on time for increase in the composite strength score (p = .002, ŋp2 = .18). There was a significant interaction of composite strength score between groups, (p = .04, ŋp2 = .08). The CM group (12.3% increase) had significantly greater improvements in composite strength from pre- to post-test than CHO (2.7% increase). There were no differences in these results based on demographic variables. Conclusion This is the first study comparing the impact of CM and CHO on athletic outcomes in an adolescent population in a field-based environment. CM had a more positive effect on strength development and should be considered an appropriate post-exercise recovery supplement for adolescents. Future research will benefit from longer study durations with larger numbers of participants.